The Effect of Implementing Tri Hita Karana-Oriented Ergosafety on the Health Quality and Productivity of Piranti Upakara Makers - Ni Luh Gede Aris Maytadewi Negara; I Putu Prisa Jaya; Gede Mahesa Paratama Dipa (Public Health Undergraduate Program, Faculty of Health Science, Universitas Pembangunan Nasional Veteran Jakarta, 2026)
Background: Ergosafety is an approach to ergonomic management that prioritizes the health, safety, and comfort of workers. Ergosafety aims to create an optimal work environment, thereby reducing the risk of injury, fatigue, and work stress, as well as increasing overall productivity and job satisfaction. The purpose of this research is to verify if the implementation of Tri Hita Karana-oriented ergosafety can be a holistic and sustainable solution to improve the quality of health and productivity of piranti upakara makers. Method: The research was conducted for six months, from July to October 2025, and adopted a quasi-experimental design with a one-group pretest-posttest design. The research subjects and the target population were piranti upakara makers in Buruan Village, Penebel District, Tabanan Regency. The accessible population was 50 workers who met the inclusion criteria. The number of research samples was 25 people, who were selected by purposive sampling. Results: The results showed that Tri Hita Karana-oriented ergosafety had a positive impact on the quality of health and work performance. This improvement was indicated by a 15.25% (p ≤ 0.01) decrease in the score of musculoskeletal complaints, a 28.3% (p ≤ 0.01) decrease in the score of work fatigue, and a 34.43% (p ≤ 0.01) increase in work productivity. Conclusion: The implementation of Tri Hita Karana-oriented ergosafety can improve the quality of health and productivity of piranti upakara makers.